Science Education for Sustainable Development, Part 2 - George, June M. (Daily Express, 2005)
In examining the potential contribution of science education to sustainable development, Pt. 2 of this article examines science education for future career scientists and seeks to point the way forward
Keywords: Science education; Education and development; Sustainable development; Scientific personnel; Scientists; Career planning; Trinidad and Tobago